Relação entre assimetria de força de membros inferiores e mudanças de direção em jogadores de futebol - Alexandre Augusto Rodrigues Alves (2017)
The relationship between bilateral asymmetry of lower limb strength and sports performance has become the focus of research in recent years. However, regarding the changes of direction in the soccer still exists a lack of scientific evidences that support this relation. The aim of this study was to investigate the level of the relationship between the asymmetry of lower limb strength and the performance of the changes of direction in soccer players. The sample consisted of twenty athletes of the sub-17 category of a professional club. The lower limb strength asymmetry for the peak force and impulse variables were measured in the counter-movement jump performed on a double force platform. The performance of the changes of direction was measured in tests 505 and L by means of three parameters: 1) total time of the test; 2) part-time of the change of direction; 3) deficit of change of direction. The level of relation between variables was defined by the linear correlation coefficient of Pearson. The level of significance was 0.05. No statistically significant correlations were found between the lower limb strength asymmetry of the peak force and impulse variables and performance of change in direction tests. It can be concluded that the asymmetry of lower limb strength measured in the countermovement jump has no relation to the total time of the 505 and L direction change tests. It was also concluded that even with the use of more precise parameters to measure performance of the ability to change direction such as the part-time change of direction and the deficit of the change of direction, its relation to bilateral asymmetry of lower limb strength does not hold